2014
DOI: 10.1038/onc.2014.23
|View full text |Cite
|
Sign up to set email alerts
|

Lysyl oxidase-like 2 (LOXL2) and E47 EMT factor: novel partners in E-cadherin repression and early metastasis colonization

Abstract: Short title: E47 and LOXL2 contribute to early metastasis Word length: 5,258 words 2 ABSTRACT Epithelial-mesenchymal transition (EMT) has been associated with increased aggressiveness and acquisition of migratory properties providing tumor cells with the ability to invade into adjacent tissues. Downregulation of E-cadherin, a hallmark of EMT, is mediated by several transcription factors (EMT-TFs) that act also as EMT inducers; among them, Snail1 and the bHLH transcription factor E47. We previously described ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 42 publications
5
79
0
Order By: Relevance
“…CCL9 is induced through TGF-β signaling in myeloid cells in the pre-metastatic lungs, whereas it enhances tumor cell survival and promotes metastasis (25). Another recent study has found that lysyl oxidase-like 2 (LOXL2) and the bHLH transcription factor E47, which function together to induce EMT, also contribute to the recruitment of BMDCs to pre-metastatic lungs through transcriptional regulation of fibronectin and cytokines including GM-CSF (26). TNFα, TGFβ, and VEGF-A secreted by the primary tumor can induce the expression of S100A8 and S100A9 in pre-metastatic lung endothelial cells which act as potent chemoattractants for Mac-1 + myeloid cells and cancer cells through SAA3-induces TLR4 signaling (17, 18).…”
Section: Traits Of a Pre-metastatic Nichementioning
confidence: 99%
See 1 more Smart Citation
“…CCL9 is induced through TGF-β signaling in myeloid cells in the pre-metastatic lungs, whereas it enhances tumor cell survival and promotes metastasis (25). Another recent study has found that lysyl oxidase-like 2 (LOXL2) and the bHLH transcription factor E47, which function together to induce EMT, also contribute to the recruitment of BMDCs to pre-metastatic lungs through transcriptional regulation of fibronectin and cytokines including GM-CSF (26). TNFα, TGFβ, and VEGF-A secreted by the primary tumor can induce the expression of S100A8 and S100A9 in pre-metastatic lung endothelial cells which act as potent chemoattractants for Mac-1 + myeloid cells and cancer cells through SAA3-induces TLR4 signaling (17, 18).…”
Section: Traits Of a Pre-metastatic Nichementioning
confidence: 99%
“…More recent work has shown that factors secreted by hypoxic tumor cells, including LOX, LOXL2, and G-CSF, direct a pro-metastatic niche reprogramming (6062). LOXL2 has also been shown to collaborate with E47 to induce EMT and increase the secretion of GM-CSF to recruit BMDCs to pre-metastatic lungs (26). VEGF, another hypoxia-induced factor, has been known to play an important role in cancer growth and metastasis through the induction of angiogenesis in the primary tumor.…”
Section: Tumor-derived Formation Of a Pre-metastatic Nichementioning
confidence: 99%
“…So, Grhl3 may directly bind to this motif to repress E-cadherin expression. Additionally, several E-cadherin transcriptional repressors, such as Twist, Zeb1, Snail, Slug, Loxl2, and E47 that directly interact with the proximal E-boxes of the promoter, have been identified in recent years [17,[26][27][28][29]. Grhl3 may also interact with these factors and bind to the E-boxes, and indirectly repress E-cadherin expression.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies against MMP and lysyl-oxidase like 2 (LOXL2) (simtuzumab) [81] are tested for liver fibrosis.…”
Section: Anti-fibrotic Therapiesmentioning
confidence: 99%